Integrated and managed grasses shape soil pore networks and carbon processes in tropical agroecosystems: Insights from synchrotron X-ray tomography - Ricardo O. Bordonal; Maoz Dor; Andrey K. Guber; Maurício R. Cherubin; Alexandre F. Nascimento; Sarah Tenelli; Newton La Scala; Carlos E.P. Cerri; João L.N. Carvalho; Alexandra N. Kravchenko (Journal of Environmental Management, 2026)

Soil and vegetation cover estimation for global imaging spectroscopy using spectral mixture analysis - Francisco Ochoa; Philip G. Brodrick; Gregory S. Okin; Eyal Ben-Dor; Thoralf Meyer; David R. Thompson; Robert O. Green (Remote Sensing of Environment, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

An accuracy assessment of the surface reflectance product from the EMIT imaging spectrometer - Red Willow Coleman; David R. Thompson; Philip G. Brodrick; Eyal Ben Dor; Evan Cox; Carlos Pérez García-Pando; Todd Hoefen; Raymond F. Kokaly; John M. Meyer; Francisco Ochoa; Gregory S. Okin; Daniela Heller Pearlshtien; et al. (Remote Sensing of Environment, 2024)

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Seismic anisotropy and stress-field variations along the Dead Sea Fault zone in northern Israel - G. Ben-Dor; I. Kurzon; R. Weinberger; M. Tsesarsky (Tectonophysics, 2024)

Remote sensing of the Earth's soil color in space and time - Rodnei Rizzo; Alexandre M.J.-C. Wadoux; José A.M. Demattê; Budiman Minasny; Vidal Barrón; Eyal Ben-Dor; Nicolas Francos; Igor Savin; Raul Poppiel; Nelida E.Q. Silvero; Fabrício da Silva Terra; Nícolas Augusto Rosin; et al. (Remote Sensing of Environment, 2023)

First confirmed record of Zu cristatus in the Mediterranean coast of Israel and the eastern shores of the Levant - DANIEL GOLANI; DOR EDELIST; ARSENIY R. MOROV; NIR STERN (Mediterranean Marine Science, 2023)
In the present paper we report the first substantiated record of the Scalloped ribbonfish Zu cristatus (Bonelli, 1819) from the Mediterranean coast of Israel. The previous unsubstantiated record from Israel was based on a juvenile specimen that was found on the shore over seven decades ago and was not saved. This report constitutes the first confirmed record of this species from the Levant.

Rapid morphological changes as agents of adaptation in introduced populations of the common myna (Acridotheres tristis) - Tali Magory Cohen; Richard E. Major; R. Suresh Kumar; Manoj Nair; Kyle M. Ewart; Mark E. Hauber; Roi Dor (Evolutionary Ecology, 2021)

Towards systematic nomenclature for cell-free DNA - Abel J. Bronkhorst; Vida Ungerer; Frank Diehl; Philippe Anker; Yuval Dor; Michael Fleischhacker; Peter B. Gahan; Lisa Hui; Stefan Holdenrieder; Alain R. Thierry (Human Genetics, 2021)
Cell-free DNA (cfDNA) has become widely recognized as a promising candidate biomarker for minimally invasive characterization of various genomic disorders and other clinical scenarios. However, among the obstacles that currently challenge the general progression of the research field, there remains an unmet need for unambiguous universal cfDNA nomenclature. To address this shortcoming, we classify in this report the different types of cfDNA molecules that occur in the human body based on its origin, genetic traits, and locality. We proceed by assigning existing terms to each of these cfDNA subtypes, while proposing new terms and abbreviations where clarity is lacking and more precise stratification would be beneficial. We then suggest the proper usage of these terms within different contexts and scenarios, focusing mainly on the nomenclature as it relates to the domains of oncology, prenatal testing, and post-transplant surgery surveillance. We hope that these recommendations will serve as useful considerations towards the establishment of universal cfDNA nomenclature in the future. In addition, it is conceivable that many of these recommendations can be transposed to cell-free RNA nomenclature by simply exchanging “DNA” with “RNA” in each acronym/abbreviation. Similarly, when describing DNA and RNA collectively, the suffix can be replaced with “NAs” to indicate nucleic acids.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Erratum to: DHEA metabolism to the neurosteroid androsterone: a possible mechanism of DHEA’s antidepressant action - Rivka Ben Dor; Christine E. Marx; Lawrence J. Shampine; David R. Rubinow; Peter J. Schmidt (Psychopharmacology, 2015)

DHEA metabolism to the neurosteroid androsterone: a possible mechanism of DHEA’s antidepressant action - Rivka Ben Dor; Christine E. Marx; Lawrence J. Shampine; David R. Rubinow; Peter J. Schmidt (Psychopharmacology, 2015)

Residency and movement patterns of Arctic charr Salvelinus alpinus relative to major estuaries - A. D. Spares; M. J. W. Stokesbury; M. J. Dadswell; R. K. O'Dor; T. A. Dick (Journal of Fish Biology, 2015)
Estuarine residency and marine movements of 43 anadromous Arctic charr Salvelinus alpinus (mean ± s.d . fork length = 523 ± 97 mm) were examined using acoustic tracking in inner Frobisher Bay ( IFB ; 63° N; 68° W), Canada, from July to September 2008 and 2009. A mean ± s.d . migration duration of 63 ± 7 days occurred from late June to early September. Detected S. alpinus were either continuously (maximum 34 days) or intermittently present in estuarine zones, on average residing approximately one third of time tracked and returning once every 9 days. Significantly higher estuarine residency during the final 15 migration days suggested that a transition phase may occur prior to freshwater re‐entry. Low travel rates during flood tide suggested individuals staged before accessing intertidal and estuarine zones. Although the two main estuaries were c. 22 km apart, 19% of tagged individuals used both. Individuals remained relatively close to freshwater overwintering systems, although late‐migration inter‐estuarine movements may have indicated natal homing. Approximately half of the individuals exhibited extra‐estuarine travel, mostly during mid‐migration, but remained within 3 km of shore ranging SLD ) of either estuary. It was concluded that IFB S. alpinus (1) spent a significant portion of their migration within or adjacent to the estuaries and (2) had a restricted marine distribution within 30 km SLD of the river mouths.

To fast or feed: an alternative life history for anadromous brook trout Salvelinus fontinalis overwintering within a harbour - A. D. Spares; M. J. Dadswell; J. MacMillan; R. Madden; R. K. O'Dor; M. J. W. Stokesbury (Journal of Fish Biology, 2014)
The seasonal feeding pattern of sea‐run brook trout Salvelinus fontinalis was studied from November to May 2010–2012 in Antigonish Harbour, Nova Scotia, Canada (45° 38′ N; 61° 55′ W). Sixty‐three S. fontinalis (mean ± s.d . fork length = 330 ± 70 mm and mass = 536 ± 351 g) captured had fed predominantly on fishes (Fundulidae and Gasterosteidae). Percentage of empty stomachs was highest during autumn (18%) and winter (22%) and lowest in spring (7%). Stomach fullness increased from autumn to a maximum during winter, relating to near‐zero body temperatures which may have effectively stopped gastric evacuation. Although feeding occurred during winter (December to March), consumption rates were calculated as negative values, and subsequently returned to positive values in spring (April to May). The over‐winter life‐history strategy of this sea‐run S. fontinalis population appears to be a feeding marine migration in which fish continually increase body condition, representing an alternative to the more common overwintering strategy of starvation in fresh water until spring.

Broad‐scale latitudinal patterns of genetic diversity among native European and introduced house sparrow ( Passer domesticus ) populations - A. W. SCHREY; M. GRISPO; M. AWAD; M. B. COOK; E. D. McCOY; H. R. MUSHINSKY; T. ALBAYRAK; S. BENSCH; T. BURKE; L. K. BUTLER; R. DOR; H. B. FOKIDIS; et al. (Molecular Ecology, 2011)
Introduced species offer unique opportunities to study evolution in new environments, and some provide opportunities for understanding the mechanisms underlying macroecological patterns. We sought to determine how introduction history impacted genetic diversity and differentiation of the house sparrow ( Passer domesticus ), one of the most broadly distributed bird species. We screened eight microsatellite loci in 316 individuals from 16 locations in the native and introduced ranges. Significant population structure occurred between native than introduced house sparrows. Introduced house sparrows were distinguished into one North American group and a highly differentiated Kenyan group. Genetic differentiation estimates identified a high magnitude of differentiation between Kenya and all other populations, but demonstrated that European and North American samples were differentiated too. Our results support previous claims that introduced North American populations likely had few source populations, and indicate house sparrows established populations after introduction. Genetic diversity also differed among native, introduced North American, and Kenyan populations with Kenyan birds being least diverse. In some cases, house sparrow populations appeared to maintain or recover genetic diversity relatively rapidly after range expansion (

Remote sensing as a tool for monitoring plasticulture in agricultural landscapes - N. Levin; R. Lugassi; U. Ramon; O. Braun; E. Ben‐Dor (International Journal of Remote Sensing, 2007)

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

The response of sea scallop ( Placopecten magellanicus ) veligers to a weak thermocline in 9-m deep mesocosms - J. L. Manuel; C. M. Pearce; D. A. Manning; R. K. O'Dor (Marine Biology, 2000)

Do larger cephalopods live longer? Effects of temperature and phylogeny on interspecific comparisons of age and size at maturity - J. B. Wood; R. K. O'Dor (Marine Biology, 2000)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Applications and performance of Radio-Acoustic Positioning and Telemetry (RAPT) systems - R. K. O'Dor; Y. Andrade; D. M. Webber; W. H. H. Sauer; M. J. Roberts; M. J. Smale; F. M. Voegeli (Hydrobiologia, 1998)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)